A Survey of the Yemeni Translation Market Needs - Alshargabi, Eman; Al-Mekhlafi, Mohammed Abdu (University of Science and Technology, Yemen, 2019)
Academic programs have changed to become learner-centered. As such, programs are based on the competences that learners should acquire. One major source for these competences is the market. The aim of this study was to identify the translation competences needed by the Yemeni market. Drawing on recent literature, the researcher developed a questionnaire, and a total number of 50 professional translators – working in Sana’a – filled the questionnaire. It included 35 items distributed to five categories: bilingual competence, cultural competence, translation competence, instrumental competence, and strategic competence, in addition to psycho-physiological components of translators. Results revealed that all translation competences were important and needed by the market; none was marked as unimportant. Specifically, 21 of them were highly important. The highest degrees of importance were for basic skills without which translation tasks can never be done: language competence, bicultural competence, problem solving procedures, and use of dictionaries and information mining. Meanwhile, the focus –though needed – was less on the competences of interpreting and modern translation technologies which can be attributed to the difficult times Yemen experiences currently that caused recession in the translation market. That was obvious in the lack of conferences and official activities, in addition to the lack of specialists in translation technology.
Keywords: Translation Competences; Market Needs; Professional Translators; Translator Training; Academic Programs